KEBIJAKAN PEMERINTAH NAJIB TUN RAZAK TERHADAP FENOMENA BRAIN DRAIN DARI MALAYSIA KE SINGAPURA TAHUN 2009-2013 - Pipit Patmawati; Faisyal Rani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Brain Drain is a Phenomenon the International migration of highly qualified persons, e.g. surgeons, physicians, scientists and engineers, from low income countries to more prosperous economies. Motive of migration brain drainer as the lack of better opportunities, upgrade of living conditions, goverment policies and better education system. This research aims to analyze the Malaysia’s Brain Drainer to the Singapura since 2009-2013, analyse the policy Najib Tun Razak the phenomenon of brain drain.The sources of data used in this research are books, journals, working papers, valid news from websites and newspaper, to describe the process by analyzing the phenomenon based on existing data.. To analyze the research question, the writer uses a perspective, specifically the perspective behavioralism, use a Teori of decision makers of Richard Snider.The crisis that occurred in the United States in 2008 resulted in economic conditions in Mlaysia also declined, with the economic downturn resulted in a much needed professionals, but professionals many migrate to the other country Therefore Najib Tun Razak make a policy, New Economic Model (NEM) and Program of Economic Transformation (ETP) and the Talent Corporation Malaysia (TalentCorp) to attact talent back.Keyword: Brain Drain, New Economic Model (NEM) and Program of Economic Transformation (ETP) and the Talent Corporation Malaysia (TalentCorp)